PURIFICATION OF FISH POND WASTEWATER FOR REUSE - Wulandari, Lies Kurniawati; Mundra , I Wayan; Hardianto; Manaha, Yosimson Petrus (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2025)
This community service-based research is simply an effort to treat household wastewater to support the availability of clean water sources in urban areas. The type of waste treated here is graywater waste, which is wastewater that comes from kitchen and bathroom sinks or washing water (not feces and urine). The reason for choosing this type of graywater waste is because of its high production, which is up to 70-75% of the total liquid waste generated from domestic activities. The method used is a physical model in the laboratory using wastewater with a model scale that uses variations in discharge, number of vetiver stems, and residence time. The study's results indicated that the filter model improved wastewater quality, producing an output that met clean water standards. This demonstrates that using wastewater treatment filters with variations in water discharge, number of rods, and residence time effectively reduces pollutants in graywater.